2018
DOI: 10.1186/s12885-018-4612-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy of lenvatinib for recurrent papillary thyroid carcinoma after multimodal treatment and management of complications: a case report

Abstract: BackgroundThe advent of tyrosine kinase inhibitors (TKIs) has changed the treatment of RAI refractory, unresectable recurrent differentiated thyroid cancer (DTC), which was formerly treated with multidisciplinary remedies.Case presentationHere we describe the case of a 64-year-old woman who underwent total thyroidectomy with tracheal resection and suffered from a recurrent tumor in the neck and multiple lung and bone metastases 3 and 11 months, respectively, after the operation. Multimodal therapies, RI (I-131… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…After the approval of lenvatinib, several studies have shown the efficacy of lenvatinib for advanced HCC in the clinical setting 14 , 15 ) . However, several fatal adverse events, including fistula formation, have been reported during the administration of mTKIs (e.g., sorafenib 16 ) , regorafenib 17 ) , and lenvatinib 18 , 19 , 20 ) ) in other cancers. In HCC treatment, there are only a few reports on fistula formation with the use of sorafenib 7 , 21 ) , and there are no reports on fistula formation during lenvatinib administration in patients with HCC.…”
Section: Introductionmentioning
confidence: 99%
“…After the approval of lenvatinib, several studies have shown the efficacy of lenvatinib for advanced HCC in the clinical setting 14 , 15 ) . However, several fatal adverse events, including fistula formation, have been reported during the administration of mTKIs (e.g., sorafenib 16 ) , regorafenib 17 ) , and lenvatinib 18 , 19 , 20 ) ) in other cancers. In HCC treatment, there are only a few reports on fistula formation with the use of sorafenib 7 , 21 ) , and there are no reports on fistula formation during lenvatinib administration in patients with HCC.…”
Section: Introductionmentioning
confidence: 99%
“…T hyroid nodules are common findings in the general population and have increased in recent years (1)(2)(3). Most thyroid nodules are actually asymptomatic and benign, and only about 5% of thyroid nodules are malignant (4)(5)(6)(7)(8). Ultrasound is the most accurate way to image thyroid nodules because malignant ultrasound features are associated with a higher malignancy risk (9).…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, patients developing recurrent or metastatic RAI refractory disease have a 10-year survival rate of only 15-20% [1,2]. Before the advent of tyrosine kinase inhibitors (TKIs), external beam radiotherapy [3,4] and volume reduction surgery were the only available remedies for RAI refractory DTC, while chemotherapy was mostly ineffective [4]. In 2014, sorafenib has been the first available multitargeted TKI [5], followed by lenvatinib, which was approved in 2015, concurring to the results of the Phase III SELECT study [6].…”
mentioning
confidence: 99%
“…Among other TKIs, lenvatinib inhibits FGFR1-4, therefore, it offers a potential chance to hamper the mechanism of resistance to the VEGF/VEGFR inhibitors. Besides, lenvatinib has a direct antioncogenic effect as it inhibits RET, thereby controlling tumor cell proliferation and blocking FGFR, and therefore modulating the tumor microenvironment [4,7,8].…”
mentioning
confidence: 99%
See 1 more Smart Citation